Mechanical, fracture toughness, and Dynamic Mechanical properties of twill weaved bamboo fiber‐reinforced Artocarpus heterophyllus seed husk biochar epoxy composite. Issue 11 (4th September 2022) - AP, Arun; Kaliappan, S.; L, Natrayan; P Patil, Pravin
Abstract: This research aimed to find the effect of Artocarpus heterophyllus fruit seed husk biochar (ASB) and twill weaved bamboo fiber (TBF) in mechanical, DMA, and fracture toughness behavior of epoxy‐based composite. The surface of both weaved bamboo fiber and biochar was treated with amino silane before composite making. In this investigation, the laminates were fabricated by hand layup process and analyzed by appropriate ASTM standards. Results of this study revealed that the incorporation of 40 vol.% twill weaved bamboo fiber (EB) into the resin improved the mechanical properties. The load distribution was uniform with twilled weaving. For composite designation EBJ3, the maximum measured tensile strength was 168 MPa, the tensile modulus is 6.24 GPa, the flexural strength is 195 MPa, and the flexural modulus is 6.85 GPa, the izod impact is 6.24 J, and the hardness is 90 shore‐D. Similarly, the maximum storage modulus and lowest loss factor for the composite designation EBJ3 were measured to be 3.8 GPa and 0.4, respectively. Moreover, the maximum measured fracture toughness and energy release rate is 39.4 MPa.√m and 0.88 MJ/m2 for composite designation EBJ3 with 5.0% biochar and 40% bamboo fibers in volume. The SEM fractography revealed that the matrix molecules are adhered to the fiber, indicating enhanced bonding. These biomass waste converted fruit seed husk biochar and industrial crop bamboo fiber epoxy composites could be used as workable material in structural, defense, automotive, and domestic product‐making applications. Abstract : Biochar preparation from Artocarpus Heterophyllus fruit seed husks.